UPAYA KANTOR PERTANAHAN DALAM MENANGGULANGI SERTIPIKAT GANDA DI KABUPATEN KUBU RAYA PONTIANAK - , Henny, S.H. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Nowadays, we may find some defect land certificates that cause land ownership dispute. One of them is the issuance of more than one certificates over a lot of land alled overlapping certificates. One of problem the overlapping certificates in Kubu Raya Pontianak regency was brought by parties to administrative court case number 15/G/2012/PTUN-PTK. The objective of this research was to identify factors causing issuance of overlapping certificates in Kubu Raya Pontianak regency and what action done by the land office in dealing with overlapping certificates in Kubu Raya Pontianak regency. It is juridical empirical research that starts from fact in research site. It begins with secondary data followed by study on primary data. The results indicate that factors causing issuance of overlapping certificates in Kubu Raya Pontianak regency is land abondened by land holder for long time, no periodic mapping by land office of Kubu Raya Pontianak regency, less carefulness of Head of village in making Letter of Land and no head of village involvement in adjudication committee. Effort done by the land office is to strengthen the use of single map system and collect data on land lots that are registered to make single digital land mapping.